DNA-In Situ Hybridization for Molecular Localization of Human Cytomegalovirus in Cervical Tissues from Iraqi Patients with Cervical Adenocarcinoma - Saad Hasan M.Ali (Journal of Global Pharma Technology, 2017)
Cervical cancer pathogenesis is a multi-factorial process where cervical epithelium is exposed to several important carcinogenic influences. On epidemiological bases, cervical cancer has the characteristics of a venereal disease and among many genital infective agents; human cytomegalovirus (HCMV) might have a role in the etiology of this neoplasm. This study aimed to investigate rate of HCMV infections in cervical aden carcinoma using DNA -in situ hybridization (DISH) and to evaluate their impact on the expressed histopathological features of those cancers. This study was designed as retrospective research. A total number of forty-nine (49) patients who had undergone hysterectomies or punch biopsies from their cervices were included. Among these, twenty-one (21) formalin-fixed paraffin-embedded tissue blocks were from cervical aden carcinoma while twenty-eight (28) cervical tissue blocks (either without any significant pathological changes or have chronic cervicitis) were included as a control groups for this study. Molecular detection of HCMV in those tissue blocks were performed by using ultra-sensitive versions of DISH technique. Human CMV DNA was found in 12 out of 21 (57.1 %) cervical adenocarcinoma tissues while no HCMV DNA was detected in any tissues from chronic cervicitis group or those in the histopathologically- healthy control group. Among those twelve positive results of Human CMV DNA –ISH reactions, eleven cases (91.7 %) of cervical adenocarcinoma have well or moderate differentiation while only one case (8.3%) was of poor grade.Keywords: Cervical adenocarcinoma, HCMV, DNA-ISH.